ON THE COMMUNICATION OF MATHEMATICAL REASONING - Bagchi, Atish; Wells, Charles (PRIMUS : problems, resources, and issues in mathematics undergraduate studies, 1998)
Presents some methods for describing and referring to mathematical objects and consistently and unambiguously signaling the logical structure of mathematical arguments. Presents the problems involved in referring to mathematics objects and properties. Discusses certain individual words used to communicate the logical structure of mathematical arguments and suggests some strategies for writing proofs. Contains 27 references. (Author/ASK)